2011
DOI: 10.2139/ssrn.1457719
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Exchange, System Size and Information Silos

Abstract: There are many technology platforms that bring benefits only when users share data. In healthcare, this is a key policy issue, because of the potential cost savings and quality improvements from 'big data' in the form of sharing electronic patient data across medical providers. Indeed, one criterion used for federal subsidies for healthcare information technology is whether the software has the capability to share data. We find empirically that larger hospital systems are more likely to exchange electronic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Prior research found that hospitals in large systems were less likely than others to exchange information with providers outside their organization, 18 and increased competition may inhibit hospitals' participation in HIOs. 16,19,23 Although our study did not find an association between market concentration and exchanges with outside providers, competition as well as limited cross-vendor interoperability may be barriers to exchanges between unaffiliated hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research found that hospitals in large systems were less likely than others to exchange information with providers outside their organization, 18 and increased competition may inhibit hospitals' participation in HIOs. 16,19,23 Although our study did not find an association between market concentration and exchanges with outside providers, competition as well as limited cross-vendor interoperability may be barriers to exchanges between unaffiliated hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…16,19,23 Although our study did not find an association between market concentration and exchanges with outside providers, competition as well as limited cross-vendor interoperability may be barriers to exchanges between unaffiliated hospitals. 18 Exchanges with unaffiliated providers and hospitals are currently limited. However, payment reform may encourage hospitals to exchange information outside their organization, including with unaffiliated hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miller and Tucker (2014a) report evidence from the AHA special survey of hospitals regarding health IT and information exchange. A key finding of that paper was that hospitals that are part of larger systems are more likely to exchange patient information electronically with other providers (hospitals and ambulatory care providers), but they are less likely to exchange information outside of their systems.…”
mentioning
confidence: 99%